Dibenzo[b, f][1, 4]oxazepines and dibenzo[b, e]oxepines: Influence of the chlorine substitution pattern on the pharmacology at the H1R, H4R, 5-HT2AR and other selected GPCRs. (November 2016) - Naporra, Franziska; Gobleder, Susanne; Wittmann, Hans-Joachim; Spindler, Julia; Bodensteiner, Michael; Bernhardt, Günther; Hübner, Harald; Gmeiner, Peter; Elz, Sigurd; Strasser, Andrea
Graphical abstract: Abstract: Inspired by VUF6884 (7-Chloro-11-(4-methylpiperazin-1-yl)dibenzo[ b, f ][1, 4]oxazepine), reported as a dual H1 /H4 receptor ligand (p Ki : 8.11 (human H1 R (hH1 R)), 7.55 (human H4 R (hH4 R))), four known and 28 new oxazepine and related oxepine derivatives were synthesised and pharmacologically characterized at histamine receptors and selected aminergic GPCRs. In contrast to the oxazepine series, within the oxepine series, the new compounds showed high affinity to the hH1 R (p Ki : 6.8–8.7), but no or moderate affinity to the hH4 R (p Ki : ≤ 5.3). For one oxepine derivative (1-(2-Chloro-6, 11-dihydrodibenzo[ b, e ]oxepin-11-yl)-4-methylpiperazine), the enantiomers were separated and the R -enantiomer was identified as the eutomer at the hH1 R (p Ki : 8.83 ( R ), 7.63 ( S )) and the guinea-pig H1 R (gpH1 R) (p Ki : 8.82 ( R ), 7.41 ( S )). Molecular dynamic studies suggest that the tricyclic core of the compounds is bound in a similar mode into the binding pocket, as described for doxepine in the hH1 R crystal structure. Moreover, docking studies of all oxepine derivatives at the hH1 R indicate that the oxygen and the position of the chlorine in the tricyclic core determines, if the R - or the S -enantiomer is the eutomer. For some of the oxazepines and oxepines the affinity to other aminergic GPCRs is in the same range as to hH1 R or hH4 R, thus, those compounds have to be classified as dirty drugs. However, one oxazepine derivative (3, 7-Dichloro-11-(4-methylpiperazin-1-yl)dibenzo[ b, f ][1, 4]oxazepine was identified as dual hH1 /h5-HT2A receptor ligand (p Ki : 9.23 (hH1 R), 8.74 (h5-HT2A R), ≤7 at other analysed GPCRs), whereas one oxepine derivative (1-(3, 8-Dichloro-6, 11-dihydrodibenzo[ b, e ]oxepin-11-yl)-4-methylpiperazine) was identified as selective hH1 R antagonist (p Ki : 8.44 (hH1 R), ≤6.7 at other analyzed GPCRs). Thus, the pharmacological results suggest that the oxazepine/oxepine moiety and additionally the chlorine substitution pattern toggles receptor selectivity and specificity.